Phage Selective Pressure Reduces Virulence of Hypervirulent Klebsiella pneumoniae Through Mutation of the wzc Gene - Song, Lingjie; Yang, Xianggui; Huang, Jinwei; Zhu, Xiaokui; Han, Guohui; Wan, Yan; Xu, Ying; Luan, Guangxin; Jia, Xu (Frontiers in Microbiology, 2021)
Hypervirulent Klebsiella pneumoniae (hvKp) is one of the major community-acquired pathogens, which can cause invasive infections such as liver abscess. In recent years, bacteriophages have been used in the treatment of Klebsiella pneumoniae, but the characteristics of the phage resistant bacteria produced in the process of phage therapy need to be evaluated. In this study, two Podoviridae phages, hvKpP1 and hvKpP2, were isolated and characterized. In vitro and in vivo experiments demonstrated that the virulence of the resistant bacteria was significantly reduced compared with that of the wild-type. Comparative genomic analysis of monoclonal sequencing showed that nucleotide deletion mutations of wzc and wcaJ genes led to phage resistance, and the electron microscopy and mucoviscosity results showed that mutations led to the loss of the capsule, meanwhile, animal assay indicated that loss of capsule reduced the virulence of hvKp. The findings can contribute to a better understanding of that bacteriophage therapy can not only kill bacteria directly, but also reduce the virulence of bacteria by phage screening.